The Alevi question and the limits of citizenship in Turkey. Issue 5 (20th October 2019) - Boyraz, Cemil
ABSTRACT: The Alevi question in Turkey is not only about a manifestation of the demands for religious freedoms and pluralism but also an issue of citizenship at least for the last three decades. This article argues that as a result of the rise of the Alevi identity and collective capacity of the Alevis to formulate demands in the national and international public spheres, the issue has increasingly turned to a matter of struggle for the long-denied equal citizenship rights of the Alevis in Turkey. Expected failure of workshops process, namely Alevi Opening, during the second term of the Adalet ve Kalkınma Partisi (AKP) period increasingly brought a sense of the disappointment among the Alevi organizations due to the fact that the issue was not managed with a perspective based on equal citizenship rights but with a discussion on the authenticity and originality of the Alevi demands. Enduring silence for the solution of the Alevi question in the last decade would lead Alevi organizations to the search for the extension of the self-creation of the survival mechanisms without the state support. This paper, within these considerations, is based on the demands of the Alevi society in Turkey and their struggle for the legal recognition, which increasingly challenged the Turkish form of secularism and citizenship regimes today.